KARAKTERISTIK MAKROALGA HIJAU Ulva lactuca ISOLAT PANTAI LOMBOK TIMUR: ANALISIS PROKSIMAT, SENYAWA BIOAKTIF, DAN POLISAKARIDA ULVAN - Ayuliansari, Yossy; Murdiah, Murdiah; Hayati, Mir’atul; Aini, Diah Miftahul; Furqon, Baiq Repika Nurul (UIN AR-RANIRY, 2026)
Ulva lactuca is a green macroalga with high potential as a source of sulfated polysaccharides and bioactive compounds; however, information on its ulvan characteristics from East Lombok waters remains limited. This study aimed to comprehensively characterize the chemical composition of Ulva lactuca collected from the coastal waters of East Lombok through proximate analysis, extraction and characterization of ulvan polysaccharides, and identification of bioactive compounds using gas chromatography–mass spectrometry (GC-MS). Proximate analysis revealed moisture content of 13.11%, protein 15.71%, lipid 0.04%, and crude fiber 45.03%, indicating a high fiber content and very low lipid level. Ulvan extraction using HCl resulted in a significantly higher yield (11.91%) compared to NaOH (3.10%) and higher sulfate content (33.75% vs 27.58%). GC-MS analysis of the methanolic extract identified various bioactive compounds predominantly belonging to fatty acids, with hexadecanoic acid (palmitic acid) as the major component, along with other compounds such as 9-octadecene, neophytadiene, and long-chain alcohol derivatives. These compounds are known to exhibit biological activities including antibacterial, anti-inflammatory, and antioxidant properties. Overall, the combination of proximate composition, ulvan content, and bioactive compound profile highlights the potential of Ulva lactuca from East Lombok as a promising source of functional food ingredients and natural bioactive substances.